(untitled) (Journal of the College of Education for Women, 2024)
The current research aims to build a measure of the sensitive personality among those working with people with special needs, and then identify the statistical significance of the differences in the level of sensitive personality among those working with people with special needs according to the variables (gender, educational attainment, housing, number of years of service). A sample was formed. The research included (425) male and female employees working with special needs in government departments in the Kurdistan Region of Iraq. They were chosen randomly. To prove the objectives of the research the researchers built a sensitive personality scale and extracted the psychometric properties of the scale The scale, in its final form consists of (76) items distributed across the scale’s domains The data was treated statistically, and the results indicated that the sample members are people with high sensitivity and there is a statistically significant difference between the average scores of the sample members according to the gender variable, in favor of female There is no statistically significant difference between the average scores of the sample members according to the achievement variable and there is a statistically significant difference according to the residence variable and in favor of Sulaymaniyah Governorate, there is a statistically significant difference according to the job variable and in favor of employees and there is no difference in according to the years of service variable, and in In light of the results, a set of recommendations and proposals were reached.